Brain stem hemorrhage due to cerebral amyloid angiopathy: The autopsy of a patient with Alzheimer’s disease at a young age - Ohtani, Seiji; Shimizu, Keiko; Asari, Masaru; Maseda, Chikatoshi; Oka, Kumiko; Yamada, Hiromi; Hoshina, Chisato; Doi, Hiroki; Yajima, Daisuke; Shiono, Hiroshi; Ogawa, Katsuhiro (Legal medicine (Tokyo, Japan), 2014)
We report findings from an autopsy of a male in his 40s who died of a brain stem hemorrhage associated with cerebral amyloid angiopathy (CAA), senile plaques (SPs) and neurofibrillary tangles (NFTs), which are histopathological changes associated with Alzheimer’s disease (AD). Our immunohistochemical study demonstrated amyloid β (Aβ) deposition in the small cerebral arteries and SPs. Although hypertension (178/132mmHg) was detected, the subject was not treated accordingly. CAA coupled with hypertension might have caused the intracerebral hemorrhage (ICH).